Motivasi Belajar dan Prestasi Akademik Mahasiswa dalam Pembelajaran Offline dan Online dalam Masa Pandemi Corona Virus Disease 2019 - Jein Jelien Tampi; Jimmy Posangi; Greta Jane Pauline Wahongan (Indonesian Journal of Public Health and Community Medicine, 2021)
Background: The Covid-19 pandemic was changed the learning methode to online so that was disrupt the education method. Factors such as physical activity, fatigue, time management to learning motivation are often the main causes. The purpose of this study was to analyzed the correlation between learning motivation and the student academic achievement in offline and online learning methods during the Covid-19 pandemic. Method: This is a correlation research. The Research respondents were students of the Faculty of Sports Science, Manado State University, class of 2017 as many as 75 respondents. The research was carried out in February-May 2021. The variables were the learning motivation and academic achivement. The questionnaires in the form of google forms as a research instruments. The data were analyzed univariately and bivariately. Results: The results showed that the motivation to learn offline with a 5th semester GPA was in good category (29.3%) and very good (70.7%). Motivation to learn online in the Covid-19 situation with a 6th semester GPA in good category (76%) and very good (24%). The results of the bivariate analysis showed that there was a correlation between learning motivation and academic achievement (p=0,001). Conclusion: The conclusion of this study is that there is a correlation between learning motivation and academic achievement.